Medial prefrontal cortex dopamine controls the persistent storage of aversive memories - Gonzalez, María C.; Kramar, Cecilia P.; Tomaiuolo, Micol; Katche, Cynthia; Weisstaub, Noelia; Cammarota, Martín; Medina, Jorge H. (Frontiers in Behavioral Neuroscience, 2014)
Medial prefrontal cortex (mPFC) is essential for initial memory processing and expression but its involvement in persistent memory storage has seldom been studied. Using the hippocampus dependent inhibitory avoidance learning task and the hippocampus-independent conditioned taste aversion paradigm together with specific dopamine receptor agonists and antagonists we found that persistence but not formation of long-tem aversive memories requires dopamine D1/D5 receptors activation in mPFC immediately after training and, depending on the task, between 6 and 12 hour later. Our results indicate that besides its well-known participation in retrieval and early consolidation, mPFC also modulates the endurance of long-lasting aversive memories regardless of whether formation of the aversive mnemonic trace requires the participation of the hippocampus.